Rough approximations in graphs using neighborhood of vertices - Shobe, Nabi; Sedghi, Shaban; Ramane, Harishchandra S. (Journal of Global Research in Mathematical Archives(JGRMA), 2015)
Rough set is a mathematical tool for dealing with uncertainty. The theory of rough sets proposed by Pawlak in 1982. Then, in 2004, Davvaz concerned a relationship between rough sets and ring theory by using the notion of ideals. Lower and upper approximations are the main subjects in rough sets. In this paper, we investigate the lower and upper approximations in a graph by using the notion of neighborhood of vertices.